Procedural Treatments for Knee Osteoarthritis: A Review of Current Injectable Therapies - Lisa M. Billesberger; Kyle M. Fisher; Yawar J. Qadri; Richard L. Boortz-Marx (Pain Research and Management)
Knee osteoarthritis is a common painful degenerative condition affecting the aging Canadian population. In addition to pain and disability, osteoarthritis is associated with depression, comorbid conditions such as diabetes, and increased caregiver burden. It is predicted to cost the Canadian healthcare system $7.6 billion dollars by 2031. Despite its high cost and prevalence, controversy persists in the medical community regarding optimal therapies to treat knee osteoarthritis. A variety of medications like nonsteroidal anti-inflammatories and opioids can cause severe side effects with limited benefits. Total knee arthroplasty, although a definitive management, comes with risk such as postoperative infections, revisions, and chronic pain. Newer injectable therapies are gaining attention as alternatives to medications because of a safer side effect profile and are much less invasive than a joint replacement. Platelet-rich plasma is beginning to replace the more common injectable therapies of intra-articular corticosteroids and hyaluronic acid, but larger trials are needed to confirm this effect. Small studies have examined prolotherapy and stem cell therapy and demonstrate some benefits. Trials involving genicular nerve block procedures have been successful. As treatments evolve, injectable therapies may offer a safe and effective pathway for patients suffering from knee osteoarthritis.